Answer:
A and C
Step-by-step explanation:
-3*3 = -9
-1*-9 = 9
-27/3 = -9
-9/-1 = 9
Answer:
(f o g)(x)= 3x + 14
(g o f)(x) = 3x + 4
Step-by-step explanation:
(f o g)(x) = f(g(x)) = f(x + 5) = 3(x + 5) - 1 = 3x + 15 - 1 = 3x + 14
(g o f)(x) = g(f(x)) = g(3x - 1) = 3x - 1 + 5 = 3x + 4
35 divided by 2 1/2
change 2 1/2 to an improper fraction
2 1/2 = 5/2
35 divided by 5/2
copy dot flip
35 * 2/5
70/5
14
you can make 14 plots
4*-5 is -20 is does not equal -25 so it’s false
Answer:
Step-by-step explanation:
3*n*p*6 = 18np